Autorregulação da aprendizagem : intervenção com alunos ingressantes do ensino superior - Freitas-Salgado, Fernanda Andrade de, 1980- (2013)
Orientadores: Soely Aparecida Jorge Polydoro, Pedro José Sales Luis da Fonseca Rosário